On the Lefkas (Ionian Sea) November 17, 2015 Mw=6.5 Earthquake Macroseismic Effects. Issue 12 (1st December 2020) - Kassaras, Ioannis; Kazantzidou-Firtinidou, Danai; Ganas, Athanassios; Tonna, Sandra; Pomonis, Antonios; Karakostas, Christos; Papadatou-Giannopoulou, Chara; Psarris, Dimitrios; Lekkas, Efthymios; Makropoulos, Konstantinos
ABSTRACT: We exploit macroseismic observations and instrumental data aiming at explaining the effects of the 17th November 2015 Mw=6.5 earthquake, occurred beneath the southwestern peninsula of Lefkas Island (Ionian Sea) causing two casualties, major geo-environmental and slight-to-moderate structural effects. The spatial distribution of the structural damage of the local building stock is well correlated with the deformation pattern deduced from satellite geodesy, it appears though considerably low with respect to the ground deformation. Comparison with the previous strong earthquake on 14.8.2003 with Mw=6.2 occurred about 20 km to the north, shows that structural damage was significantly lower during the recent quake and also manifests good behaviour of the local buildings. This is partly explained by the characteristics of the ground motion and primarily explained by the unique concepts applied to the non-engineered buildings of Lefkas to resist ground motions.